The Influence Of Investigative Audits To Improve Financial Accountability In Government Institutions - Sonang Ramena Sipahutar; Desmorina Sianturi; Nur Fadilla; Rosinta Simatupang; Galih Supraja (Penerbit Jurnal Indonesia, 2025)
This study discusses the role of investigative audits in strengthening financial accountability in government institutions. Investigative audits have an important function in detecting corruption, abuse of power, and financial statement discrepancies. Using a quantitative approach, data were obtained through surveys and in-depth interviews involving auditors and government officials. The findings show that investigative audits can improve transparency, efficiency, and public trust in the financial management of government agencies. Recommendations include strengthening auditor capacity and implementing investigative audits in an integrated manner within the internal control system to improve accountability.